Impact of leading presenting symptoms on the diagnostic performance of high-sensitivity cardiac troponin T and on outcomes in patients with suspected acute coronary syndrome - Biener, Moritz; Müller-Hennessen, Matthias; Vafaie, Mehrshad; Katus, Hugo; Giannitsis, Evangelos (Clinical chemistry, 2015)
BACKGROUND: Diagnostic performance of high-sensitivity cardiac troponin T (hs-cTnT) varies depending on presenting symptoms in patients with suspected acute coronary syndrome (ACS). METHODS: We compared performance measures of hs-cTnT among patients admitted to the emergency department with typical chest pain (angina), dyspnea, and atypical symptoms and assessed outcomes by leading presenting symptoms. RESULTS: A total of 658 patients suspected of ACS and presenting with typical chest pain (n = 241, 36.6%), dyspnea (n = 142, 21.6%), or atypical symptoms (n = 275, 41.8%) were included. Diagnostic accuracy of hs-cTnT on admission was higher among patients with typical chest pain compared to those with atypical symptoms [area under the curve (AUC) 0.823 vs AUC 0.776 vs AUC 0.705, P > 0.05 and P = 0.04]. Absolute concentration changes within 6 h improved accuracy among all subgroups, with the smallest added benefit in typical chest pain and dyspnea (ΔAUC, 0.078; P = 0.02 and 0.05, P > 0.05). During 1-year follow-up, dyspnea was associated with a higher risk of death (hazard ratio, 2.36; 95% CI, 1.26-4.43, P = 0.008) and death/AMI (hazard ratio, 2.23; 95% CI, 1.21-4.11, P = 0.01) compared to typical chest pain. Optimal discriminating values for hs-cTnT were higher among patients presenting with dyspnea compared to those with typical chest pain (91.2 vs 14.1 ng/L, P < 0.001). CONCLUSION: The diagnostic performance of hs-cTnT in patients with suspected ACS depends on the leading presenting symptom. Patients admitted with dyspnea represent a high-risk cohort in which the diagnosis of ACS is less frequent and with inferior performance of serial hs-cTnT measurements. Higher hs-cTnT cutoffs at baseline and absolute changes after 6 h help to identify non-STEMI (ST segment elevation myocardial infarction) in this population.